Ozoniotherapy as a supporting option in orofacial harmonization – a narrative literature review (Research, Society and Development, 2023)
Ozone has been considered a complementary therapy in several areas of dentistry, such as endodontics, semiology and dentistry. Specifically in the area of orofacial harmonization, ozone has stood out for its excellent action as a germicide and biostimulator. Its germicidal capacity has been widely researched, while its biostimulating action is highly valued due to its biocompatibility, which is fundamental for a safe treatment. The number of cases reporting unwanted effects with ozone is low, making it an attractive point for its use in dentistry. Due to the increasing use of ozone, this narrative review of the literature aimed to present the applicability of ozone therapy in the specialty of orofacial harmonization, in addition to guiding dentists on the use of ozone in clinical practice. Searches were carried out in PubMed, LILACS and Scielo databases, with the descriptors "Ozone", "Dentistry" and "Therapeutic Uses". Boolean operators were used to correlate terms, with no restriction on the type of article to be included in the references, but with a publication date limitation of 14 years. The analysis of the articles was qualitative, integrating any research methodology related to the terms. It is concluded with this literature review research that ozone has a wide applicability in the specialty of successful orofacial harmonization, either for its germicidal or biostimulating action, and, when applied by a qualified professional, the result is very effective. Its forms of presentation described in the literature are in gas, ozonized water or oil (ozonide), which offer a huge range of treatments applied to clinical practice. It should be noted, however, that further studies are needed to expand knowledge in the area.